Model Pembelajaran Pendidikan Kewarganegaraan Sebagai Pendidikan Nilai Moral di Sekolah Dasar - Nurfaizah AP (Publikasi Pendidikan, 2017)
Seeing the condition of many moral values, so the role of teachers / educators and designers in the field of values and moral education is necessary. The problem that arises is how can values and moral education be communicated to the students and which learning model is appropriate? Citizenship Education is one form of values education, which in the delivery of learning needs to show some models. Some models of values and education will help us understand moral education and help students practice practicing the moral values they learn in school.Keyword: Citizenship Education, values education